Assessing vertical distribution of organic carbon stocks in shallow soils under a bush-encroached rangeland - Masotla, Abel Lesetja (My University, 2021)
Globally and in most parts of South Africa, there is a trend of increasing shrub encroachment in savanna rangelands. A number of studies have investigated the impact of shrub encroachment on soil organic carbon content (SOC) and soil organic carbon stocks (SOCs) in savannas. So far there is no clear consensus on whether shrub encroachment increases or decreases the level of SOC and SOCs, especially in semi arid savanna grasslands. Furthermore, knowledge on the effects of shrub encroachment on SOCs is largely restricted to the topsoil, as this is the part of the profile influenced by inputs and losses of soil organic matter. How shrub encroachment affects the vertical distribution of SOCs is rarely considered in the existing literature and the edaphic factors controlling SOCs with depth are poorly understood. The objectives of this study were (i) to quantify the vertical distribution of SOC and SOCs and (ii) to identify the edaphic factors controlling the vertical distribution of SOC and SOCs in a shrub-encroached savanna grassland sited on shallow plinthic soil. To achieve the objectives, a vegetation and soil survey of the savanna grassland was conducted whereby sampling areas were demarcated and characterized into open and shrub encroached grassland plots. In each encroachment level, three pits were randomly dug to the limiting layer on plots sited on the same soil type and similar topographic position. Soil samples were collected from the pits at depth intervals of 0-10, 10-20, 20-30, 30-40, 40-50, 50-60 and 60-70 cm. The collected soil samples were analyzed for chemical and physical properties in the laboratory. Correlation analysis was carried out to determine the relationship between SOC and SOCs, which were the variables of interest in this study and related controlling soil physicochemical properties. The results showed that SOC was significantly greater (P<0.05) in the shrub-encroached grassland compared to open grassland. Furthermore, the results revealed that SOC was on average 19 and 13% greater in the topsoil (0-20 cm) and subsoil (20-70 cm) of shrub encroached grassland compared to open grassland. The greater SOC in the topsoil of the shrub-encroached grassland was mainly attributed to higher SOC inputs from plant litter and detritus derived from trees and grasses, which are the dominant plant life forms in savannas. In the topsoil, SOC and SOCs were positively correlated with extractable phosphorus (P) (r = 0.60; P < 0.05), while in the subsoil they were positively correlated ix with extractable phosphorus (r = 0.54), soil porosity (r = 0.52), extractable copper (r = 0.46), extractable zinc (r = 0.41), exchangeable calcium (r = 0.37) and negatively correlated with mean weight diameter (r = -0.43). Overall, SOC and SOCs under both shrub-encroached and open grasslands vertically decreased with soil depth. The results obtained highlighted that the factors controlling the level of SOC and SOCs differs in the topsoil and subsoil of the studied shrub encroached grassland. These findings suggest that in the shallow plinthic soil investigated in this study, SOC in the topsoil is controlled by the macronutrient P, while in the subsoil it is physically protected by soil aggregates and chemically stabilized via complexation interactions with exchangeable cations and heavy metals. In-depth understanding of the physico-chemical factors controlling SOC storage is critical to foster management practices that will improve the cycling of SOC in shrub-encroached savanna grasslands.
Thesis (M. Sc. Agriculture (Soil Science)) -- University of Limpopo, 2021
Keywords: Soil; Shrub encroachment; Savanna rangelands; Soil organic carbon content; Soils -- Carbon content; Savanna ecology; Shrublands; Rangelands; Soil ecology; Organic compounds; Soils -- Organic compound content